Karakterisasi Zeolit Alam Asal Pantai Manikin, Kabupaten Kupang, Nusa Tenggara Timur - Faustina De Yesu Prisila Abi; Dionisia Hariani Nada; Anggelinus Nadut; Gertreda Latumakulita; Maximus M. Taek (Lembaga Bale Literasi, 2025)
Natural zeolite from Manikin (ZAM), Kupang Regency, has been successfully characterized by XRF, FTIR-ATR, powder-XRD and SEM. XRF results show that the three most abudant elements in ZAM are Si (68.1%); Fe (11.9%) and K (9.76%). Meanwhile, there is absorption at wave number 100.45 cm-1 which indicates the presence of asymmetric O-Si-O and O-Al-O. Based on the XRD diffraction pattern of the powder analyzed by the rietvield method, it shows that ZAM consists of SiO2 and mordenite-type zeolite minerals complexed with Na and Ca metals. As for morphology of ZAM, it consists of various shapes and one of them is sharp like a needle.